The Drawings Digitalization Effectiveness In Interior Fabrication In A Philosophical Context - Tri Susetyo Andadari; Rudyanto Soesilo (Universitas Katolik Soegijapranata, 2022)
Architectural digitization has been carried out substantially, at the design stage and also at the implementation. Not only related to the design of the building’s facade but also to the interior of the building. The goal indeed is to simplify and accelerate the architect’s work. In fact, the current digitalization drawings, specifically in the realm of interior fabrication, require several additional steps becomes a product.This research uses literature study method with descriptive evaluative analysis to describe as broadly as possible issues related to the effectiveness of digitalization drawings in interior fabrication in philosophical studies based on ontology, epistemology and axiology. The study was carried out using empirical and theoretical phenomena as well as examining the ideas behind the effectiveness of digitizing drawing (in interior fabrication) to its application.The final result shows that the research concept on the effectiveness of digitizing drawings in interior fabrication is empirical, rationalist, and measurable research as a logical science and is a part of science.